Combination of Modisco and Acupressure in Toddler Weight Gain: Kombinasi Modisco dan Akupresur Dalam Peningkatan Berat Badan Balita - Widowati , Hesty; Hanum , SMF; Widanti , Herista Novia (Procedia of Social Sciences and Humanities, 2022)
. The problem of malnutrition in children is still a significant problem in Indonesia, such as low body weight, very thin children (wasting) and stunting. One of the causes of malnutrition in children in Indonesia is the practice of feeding and complementary foods that are not yet appropriate. Various efforts can be made to improve the nutritional status of toddlers, one of which is by providing additional food in the form of Modisco (Modified Dietetic Skimmed Milk and Coconut Oil), besides that acupressure therapy has been shown to stimulate appetite in children and ultimately increase child weight. The purpose of this study was to determine the effectiveness of the combination of giving fashionableco and acupressure on increasing the weight of underweight toddlers. This study uses a pre experimental design with a one group pre post test approach. Respondents are children aged 1-5 years who are included in the thin category according to BB/TB. The number of samples was 15 toddlers, the intervention carried out was giving fashionableco for 14 days and acupressure 6 times (2 times a week for 3 weeks). The pretest was carried out before the intervention by weighing the body weight, then the posttest was carried out 1 day after the last acupressure massage by weighing the body weight again. The results of statistical tests using the Paired Sample T test obtained an average of 10.20 ± 1.10 before being given treatment and 10.74 ± 1.25 after being given treatment with a p value of 0.001 (p < 0.005), which means that the combination of fashionableco with acupressure can increase body weight in underweight toddlers.